Effect of self-alkalization on nitrite accumulation in a high-rate denitrification system: Performance, microflora and enzymatic activities. (1st January 2016) - Li, Wei; Shan, Xiao-Yu; Wang, Zhi-Yao; Lin, Xiao-Yu; Li, Chen-Xu; Cai, Chao-Yang; Abbas, Ghulam; Zhang, Meng; Shen, Li-Dong; Hu, Zhi-Qiang; Zhao, He-Ping; Zheng, Ping
Abstract: The self-alkalization of denitrifying automatic circulation (DAC) reactor resulted in a large increase of pH up to 9.20 and caused a tremendous accumulation of nitrite up to 451.1 ± 49.0 mgN L −1 at nitrate loading rate (NLR) from 35 kgN m −3 d −1 to 55 kgN m −3 d −1 . The nitrite accumulation was greatly relieved even at the same NLR once the pH was maintained at 7.6 ± 0.2 in the system. Enzymatic assays indicated that the long-term bacterial exposure to high pH significantly inhibited the activity of copper type nitrite reductase (NirK) rather than the cytochrome cd 1 type nitrite reductase (NirS). The terminal restriction fragment length polymorphism (T-RFLP) analysis revealed that the dominant denitrifying bacteria shifted from the NirS-containing Thauear sp. 27 to the NirK-containing Hyphomicrobium nitrativorans strain NL23 during the self-alkalization. The significant nitrite accumulation in the high-rate denitrification system could be therefore, due to the inhibition of Cu-containing NirK by high pH from the self-alkalization. The results suggest that the NirK-containing H . nitrativorans strain NL23 could be an ideal functional bacterium for the conversion of nitrate to nitrite, i.e. denitritation, which could be combined with anaerobic ammonium oxidation (Anammox) to develop a new process for nitrogen removal from wastewater. Graphical abstract: Highlights: 22.3% of the influent NO 3 − accumulated as NO 2 − in high-load denitrifying system at pH of 9.2. NO 2 − accumulation vanished once pH was adjusted to neutral value in high NLR system. Hyphomicrobium replaced Thauera as dominant genus after long-term exposure to high alkalinity. High pH caused a signiﬁcant inhibition to the activity of NirK rather than NirS.